Effect of organic acids on biofilm formation and quorum signaling of pathogens from fresh fruits and vegetables. (October 2017) - Amrutha, Balagopal; Sundar, Kothandapani; Shetty, Prathapkumar Halady
Abstract: Organic acids are known to be used as food preservatives due to their antimicrobial potential. This study evaluated the ability of three organic acids, namely, acetic acid, citric acid and lactic acid to manage E. coli and Salmonella sp. from fresh fruits and vegetables. Effect of these organic acids on biofilm forming ability and anti-quorum potential was also investigated. The effect of organic acids on inactivation of E. coli and Salmonella sp. on the surface of a selected vegetable (cucumber) was determined. The minimum inhibitory concentration of the organic acids were found to be 1.5, 2 and 0.2% in E. coli while it was observed to be 1, 1.5 and 1% in Salmonella sp. for acetic, citric and lactic acids respectively. Maximum inhibition of biofilm formation was recorded at 39.13% with lactic acid in E. coli and a minimum of 22.53% with citric acid in Salmonella sp. EPS production was affected in E. coli with lactic acid showing reduction by 13.42% while citric acid and acetic acid exhibited only 6.25% and 10.89% respectively. Swimming and swarming patterns in E. coli was notably affected by both acetic and lactic acids. Lactic and acetic acids showed higher anti-quorum sensing (QS) potential when compared to citric acid. 2% lactic acid showed a maximum inhibition of violacein production by 37.7%. Organic acids can therefore be used as potential quorum quenching agents in food industry. 2% lactic acid treatment on cucumber demonstrated that it was effective in inactivating E. coli and Salmonella sp. There was 1 log reduction in microbial count over a period of 6 days after the lactic acid treatment. Thus, organic acids can act as effective potential sanitizers in reducing the microbial load associated with fresh fruits and vegetables. Highlights: Organic acids are efficient inhibitors against E. coli and Salmonella spp. from fresh fruits and vegetables. Biofilm formation and quorum signaling were considerably reduced by the organic acids. Lactic acid was the most efficient organic acid in inactivating the pathogens. Organic acids can replace the chemical sanitizers in fresh produce industry, thereby maintaining food safety.